Increased Chronic Urothelial Inflammation and its Association with Urinary Tract Infection - Tauheed Farid, Ibrahim Ahmad, Mati Ur Rehman, Farooq Malik, Safiullah Sohu, Qurat-Ul-Ain Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Inflammation of the bladder can be due to both noninfectious and infectious etiologies. The most common cause of infectious cystitis has been Escherichia coli. Objectives: The basic aim of the study is to find the increased chronic urothelial inflammation and its association with urinary tract infection. Material and methods: This cross sectional study was conducted in Ganga Ram hospital, Lahore during June 2020 to December 2020. The data was collected from 50 patients. Bladder symptoms and lower urinary tract conditions were investigated. All patients were treated actively according to the latest urine culture and followed by antimicrobial prophylaxis for at least 1 month. Results: The data was collected from 50 patients. The mean age was 45± 3.56 years for male and 52.3 ± 8.89 years for females. The analysis of data shows the differences in urodynamic variables between the control subjects and the ESRD/CKD patients. Conclusion: It is concluded from our study that increased urothelial inflammation and apoptosis and decreased cell expression were found in patients with ESRD/CKD.